Long chain lipid hydroperoxides increase the glutathione redox potential through glutathione peroxidase 4 - Corteselli, Elizabeth M.; Gibbs-Flournoy, Eugene; Simmons, Steven O.; Bromberg, Philip; Gold, Avram; Samet, James M. (Biochimica et biophysica acta. General subjects, 2019)
Peroxidation of PUFAs by a variety of endogenous and xenobiotic electrophiles is a recognized pathophysiological process that can lead to adverse health effects. Although secondary products generated from peroxidized PUFAs have been relatively well studied, the role of primary lipid hydroperoxides in mediating early intracellular oxidative events is not well understood. Live cell imaging was used to monitor changes in glutathione (GSH) oxidation in HAEC expressing the fluorogenic sensor roGFP during exposure to 9-hydroperoxy-10E,12Z-octadecadienoic acid (9-HpODE), a biologically important long chain lipid hydroperoxide, and its secondary product 9-hydroxy-10E,12Z-octadecadienoic acid (9-HODE). The role of hydrogen peroxide (H2O2) was examined by direct measurement and through catalase interventions. shRNA-mediated knockdown of glutathione peroxidase 4 (GPx4) was utilized to determine its involvement in the relay through which 9-HpODE initiates the oxidation of GSH. Exposure to 9-HpODE caused a dose-dependent increase in GSH oxidation in HAEC that was independent of intracellular or extracellular H2O2 production and was exacerbated by NADPH depletion. GPx4 was involved in the initiation of GSH oxidation in HAEC by 9-HpODE, but not that induced by exposure to H2O2 or the low molecular weight alkyl tert-butyl hydroperoxide (TBH). Long chain lipid hydroperoxides can directly alter cytosolic EGSH independent of secondary lipid oxidation products or H2O2 production. NADPH has a protective role against 9-HpODE induced EGSH changes. GPx4 is involved specifically in the reduction of long-chain lipid hydroperoxides, leading to GSH oxidation. These results reveal a previously unrecognized consequence of lipid peroxidation, which may provide insight into disease states involving lipid peroxidation in their pathogenesis. •Fatty acid peroxidation is an important process in normal and pathophysiology.•Lipid hydroperoxide 9-HpODE induces GSH oxidation sensed by roGFP.•9-HpODE-induced GSH oxidation is independent of secondary products or H2O2.•GPx4 mediates 9-HpODE but not H2O2 or shorter hydroperoxide induced GSH oxidation.